2012
DOI: 10.3892/mmr.2012.869
|View full text |Cite
|
Sign up to set email alerts
|

Effects of astragaloside IV on eosinophil activation induced by house dust mite allergen

Abstract: Abstract. Astragaloside IV (AS-IV) has been noted for its reduction of eosinophilic airway inflammation in a murine model of chronic asthma. To gain a better understanding of the mechanisms involved in this anti-inflammatory phenomenon, the effect of AS-IV on human blood eosinophils was studied in vitro. Eosinophils were isolated from the blood of patients with mild atopic asthma, preincubated with AS-IV for 1 h and stimulated in the presence or absence of the house dust mite allergen Dermatophagoides pteronys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…29 Der p 1 also can activate eosinophils to release proinflammatory mediators 324 and it can prolong their survival. 325 It has 80% homology with Der f 1. The crystal structures of natural Der p 1 and Der f 1 in complex with a monoclonal antibody, 4C1, was shown to bind to a unique cross-reactive epitope on the 2 allergens that is associated with IgE recognition.…”
Section: Step 1: Determine the Region Of The Country And If Housing Tmentioning
confidence: 99%
“…29 Der p 1 also can activate eosinophils to release proinflammatory mediators 324 and it can prolong their survival. 325 It has 80% homology with Der f 1. The crystal structures of natural Der p 1 and Der f 1 in complex with a monoclonal antibody, 4C1, was shown to bind to a unique cross-reactive epitope on the 2 allergens that is associated with IgE recognition.…”
Section: Step 1: Determine the Region Of The Country And If Housing Tmentioning
confidence: 99%
“…Besides, some studies showed AS-IV attenuates the eosinophilic infiltration in ovalbumin-induced asthma (Du et al, 2008;Gu, Jiang, Wang, Du, & Cai, 2012;Huang, Tang, Wang, & Song, 2014). Previous study used 20-40 mg/kg doses of astragaloside IV (AS-IV) daily to treat OVA-induced mouse model of asthma and had different degree levels to inhibit asthma syndrome (Jin et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The blockade of CCR3 has been shown to result in a reduction of eosinophilic infiltration in animal models of asthma [ 57 ]. A study has shown that astragaloside can block CCR3 [ 58 ]. We guess that the reason AS-IV can prevent the activation of the eotaxin/CCR3 signaling pathway to reduce the infiltration of eosinophils in the airway of asthmatic mice is that it downregulates the expression of CCR3 protein and reduces cytokines such as IL-4, IL-5, and IL-13 and chemokine eotaxin [ 57 , 58 ].…”
Section: Mechanism Of Astragaloside IV In the Treatment Of Asthmamentioning
confidence: 99%